2020
DOI: 10.1186/s13104-020-05307-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin A on intestinal mucosal injury in pediatric patients receiving hematopoietic stem cell transplantation and chemotherapy: a quasai-randomized trial

Abstract: Objective Vitamin A is involved in maintenance of gut mucosal integrity and normal immune function. However, it is unclear whether these functions of vitamin A have any beneficial effects in patients undergoing hematopoietic stem cell transplantation (HSCT). In this study, we aimed to examine the potential protective effect of vitamin A supplementation on gastrointestinal (GI) mucosal integrity in HSCT recipients using plasma citrulline as a surrogate marker of intestinal integrity. Results We performed a qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The retinoyl β-glucuronide, a retinoid that is retinoic acid, was upregulated by Goji and its trained microbiota. It is a naturally occurring, biologically active metabolite of vitamin A. Retinol is vital to maintaining the integrity of the epithelium and mucous membranes ( 60 ). Previous studies showed that symbiotic bacteria produced retinol derivatives that could protect the intestinal epithelial barrier ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retinoyl β-glucuronide, a retinoid that is retinoic acid, was upregulated by Goji and its trained microbiota. It is a naturally occurring, biologically active metabolite of vitamin A. Retinol is vital to maintaining the integrity of the epithelium and mucous membranes ( 60 ). Previous studies showed that symbiotic bacteria produced retinol derivatives that could protect the intestinal epithelial barrier ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Thornley et al ( 2004) [63] demonstrated an OM incidence and severity reduction along with lower regimen-related toxicity (especially in high-risk patients) thanks to a preparation made of ursodeoxycholic acid, vitamin E, folinic acid and administered as parenteral nutrition as prevention. In contrast, Pattanakitsakul et al (2020) [68] proved in their preliminary quasi-randomized trial that vitamin A did not prevent OM.…”
Section: Paediatric Evidencementioning
confidence: 92%
“…Vitamins were another group that was analysed in different studies (seven articles found) [29,31,63,65,66,68].…”
Section: Other Dietary Components or Prevention Methodsmentioning
confidence: 99%
See 2 more Smart Citations